MINGTEPA VILLAGE DURING THE TIMURID ERA - Shakhlokhon Khusanova Artikaliyevna (Western European Studies, 2026)
This article provides information about the location of the village of Mingtepa during the Timurid era, the reign of Zahiriddin Muhammad Babur in Andijan, his struggle against Uzun Hassan and Ahmad Tanbal, who occupied Andijan after his return from Samarkand, and the participation of the people of Mingtepa in the battles against them. The article also provides some information about the social and economic situation of the village of Mingtepa during the Timurid era
Keywords: Mingtepa village; Temurids; Zahiriddin Muhammad Babur; Andijan